History :an introduction to theory, method and practice - Claus, Peter (Routledge, 2017)
"Familiarizes the reader with the varied spectrum of historical approaches. Global in scope, covering a wide range of topics from the ancient and medieval worlds to the twenty-first century"--Provided by the publisher.